A qualitative evaluation of general practitioners' perceptions regarding access to medicines in New Zealand. Issue 2 (28th March 2012) - Babar, Zaheer-Ud-Din; Grover, Piyush; Butler, Rachael; Bye, Lynne; Sheridan, Janie
Abstract : Objective: The objective of this study was to evaluate general practitioners' (GPs) perceptions regarding access to medicines in New Zealand. Design: Qualitative. Setting: Primary care. Participants: GPs. Main outcome measures: GPs' views and perceptions. Results: GPs were of the view that the current range of medicines available in New Zealand was reasonable; however, it was acknowledged that there were some drugs that patients were missing out on. When considering the range of subsidised medicines available in New Zealand, some GPs felt that there had been an improvement over recent years. It was highlighted that unexpected funding changes could create financial barriers for some patients and that administrative procedures and other complexities created barriers in receiving a subsidy for restricted medicines. GPs also reported problems with the availability and sole supply of certain medicines and claimed that switching from a branded medicine to its generic counterpart could be disruptive for patients. Conclusions: The research concluded that although there were some issues with the availability of certain drugs, most GPs were satisfied with the broader access to medicines situation in New Zealand. This view is to contrary to the situation presented by the pharmaceutical industry. The issues around sole supply, the use of generic medicines and the administrative barriers regarding funding of medicines could be improved with better systems. The current work provides a solid account of what GPs see as the advantages and disadvantages of the current system and how they balance these demands in practice.